Dance as Representative Body Language of Various Amazonian Cultures - Alejandra Longa-López R.; Quezada-Sarmiento, Pablo Alejandro; Chango-Cañaveral P.M.; Castillo-Naranza R.D. (My University, 2024)
Music and dance, as expressions of human emotion, play a key role in the different formation of people, since it allows them to happily interact and share spaces that will transcend the structure of their tastes and experiences to form an expression of art of critical attitude, the fact that it can bear fruit. In Pastaza, the cradle of 7 nationalities is fundamentally a place of diverse social and cultural interaction, in which there are different interests and motivations that must be addressed, such as complexity and heritage, heterogeneity, and diversity. The fundamental elements of collective construction, its ability to create diversity beyond the walls of the school, significantly affect the sociocultural environment. These are respected peoples that, although they have changed many customs, such as clothing and language for distinct reasons, they still take pride in their past and present as a true example for the various ethnic communities of Ecuador, because “civilization” does not mean abandoning the historical and cultural baggage of our existence. Starting from this reality, it is intended to use the artistic and cultural details of our original typical costumes as inspiration for this work through research work to rescue artisanal techniques such as seeds, feathers, clothing, and accessories, to later capture the movements of the body on stage. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.
Keywords: Economy; Health; Latin America; Sustainable development; Tourism